A New Hope on the Horizon for Kidney and Cardiovascular Protection with SGLT2 Inhibitors, GLP-1 Receptor Agonists, and Mineralocorticoid Receptor Antagonists in Type 2 Diabetic and Chronic Kidney Disease Patients - Spasovski, Goce; Rroji, Merita; Hristov, Goce; Bushljetikj, Oliver; Spahia, Nereida; Rambabova Bushljetic, Irena (Mary Ann Liebert Inc, 2024)
Type 2 diabetes (T2D) is the leading cause of chronic kidney disease (CKD). In addition, the cardiovascular prevalence in diabetic patients is around 32.2%, with a two-fold increased mortality risk compared to those without diabetes. Recent investigations have shed light on the promising cardioprotective and nephroprotective benefits of sodium—glucose cotransporter-2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1RA), and nonsteroidal mineralocorticoid receptor antagonists (nsMRAs) for individuals with T2D. The evidence robustly indicates that SGLT2i and GLP-1RA significantly reduce the risk of CKD and cardiovascular disease (CVD), all while effectively managing blood glucose levels. Furthermore, combining SGLT2i with nsMRAs amplifies the benefits, potentially offering a more profound reduction in cardiovascular and renal outcomes. The data analysis strongly supports the integration of these pharmacological agents in the management strategies for CKD and CVD prevention among T2D patients, highlighting the importance of awareness among nephrologists, especially in regions with limited healthcare resources.